Diseño y construcción de un reactor para la producción de biodiesel a partir de aceites de cocina usados. - Guevara Elizalde, Hector Ademir (2011)
The investigation has as purpose to design and to build a technological model to produce an alternating fuel starting from the kitchen oils used as measure alternative to mitigate the negative effects that cause the use of the fossil fuels, one of these effects it is the heating of the atmosphere that is the main environmental challenge that today the humanity confronts at world level. The present investigation work is related with the possibility of using an alternative fuel (Biodiesel) that is able to reduce the concentration of polluting gases as the dioxide of carbon and the methane, in the atmosphere, and at the same time to make less the dependence of the fossil fuels reducing its use, besides solving the problem of the environmental contamination that you/they cause the used kitchen oils. For the elaboration of the biodiesel it has been designed and built a reactor, in which you can store the vegetable oil and to mix it with an alcohol, he/she is also here carried out the process of laundry of the biodiesel; also, in this the students of the career of Engineering in Electromechanical will be able to carry out practices on the biodiesel elaboration, inside the unit of alternative energy.